2014
DOI: 10.3201/eid2008.130550
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia crociduraeInfection in Acutely Febrile Patients, Senegal

Abstract: As malaria cases in Africa decline, other causes of acute febrile illness are being explored. To determine incidence of Borrelia crocidurae infection during June 2010–October 2011, we collected 1,566 blood specimens from febrile patients in Senegal. Incidence was high (7.3%). New treatment strategies, possibly doxycycline, might be indicated for febrile patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 13 publications
(16 reference statements)
2
32
0
Order By: Relevance
“…8 Recent studies performed in western sub-Saharan Africa have shown the role of emergent and fastidious bacteria, such as Rickettsia felis, Coxiella burnetii, Tropheryma whipplei, Borrelia crocidurae, and Bartonella spp., as the cause of fever. [9][10][11][12][13][14][15] Rickettsia felis and Borrelia duttonii were also found in eastern Africa. [16][17][18] Some of them had already been described in Gabon.…”
Section: Introductionmentioning
confidence: 95%
“…8 Recent studies performed in western sub-Saharan Africa have shown the role of emergent and fastidious bacteria, such as Rickettsia felis, Coxiella burnetii, Tropheryma whipplei, Borrelia crocidurae, and Bartonella spp., as the cause of fever. [9][10][11][12][13][14][15] Rickettsia felis and Borrelia duttonii were also found in eastern Africa. [16][17][18] Some of them had already been described in Gabon.…”
Section: Introductionmentioning
confidence: 95%
“…Blood obtained by cardiac puncture 5 days postinoculation was tested by immunofluorescence assay incorporating P6D9 or P3A10 as described above. 15 Six blood smears from patients diagnosed by real-time PCR with B. crocidurae relapsing fever and from two patients negative for B. crocidurae in Senegal 26 were analyzed by immunofluorescence assay incorporating P6D9 or P3A10.…”
Section: Methodsmentioning
confidence: 99%
“…15,21,22 Recent studies have shown that fastidious and emerging bacteria were involved in nonmalarial fever in Africa. [13][14][15][16][17][18][19][20] Thus, our study aimed mainly using molecular analyses to look for these bacteria (Borrelia spp., Bartonella spp., T. whipplei, and C. burnetii), but we also aimed to detect the presence of malaria and other more common bacteria such as Staphylococcus aureus, Streptococcus pneumoniae, Streptococcus pyogenes, and Salmonella spp. However, as the volume of DNA extracts is limited, our search for other common bacteria such as Escherichia coli and Klebsiella pneumoniae was restricted.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Borrelia spp., Rickettsia spp., Tropheryma whipplei, and Coxiella burnetii have been detected in blood specimens from febrile patients in subSaharan Africa. [13][14][15][16][17][18][19][20] In Gabon, as in other sub-Saharan African countries, management of febrile illnesses is difficult. A recent study reported that more than 40% of patients who received antimalarial treatment in Libreville, an urban area of Gabon, had a malaria-negative test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation